Team projects in a Systems Analysis and Design class: elements of success. (21st July 2008) - Ugray, Zsolt; Hauser, Karina; Olsen, David
An essential part of many Systems Analysis and Design capstone courses is the development of operational, meaningful and real-world information systems. The development of such systems typically takes place in a small group setting to realistically simulate the future work environment of Management Information System (MIS) students. We investigated how previous work experience, time spent on the project, project complexity, and the relationships among project team members and between team members and project stakeholders affected the outcome of the system development projects. Our findings indicate that three factors: prior work experience in information technology; experience with project management; the ability to select relatively simple projects positively affected the project outcome. While difficulties among team members showed a negative impact on the outcome of the projects, difficulties in the relationships with the stakeholders and total time spent on the project did not have significant effects.